Students Perception on the use of Social Media in Learning English as a Foreign Language (EFL): Persepsi Siswa terhadap Penggunaan Media Sosial dalam Pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL) - Aryanti, Fhebby Novit; Amin, Muhammad; Thohir, Lalu (Program Studi Pendidikan Bahasa Inggris, 2024)
ABSTRACT The purpose of this research is to find out the students’ perceptions of using social media in learning English as a foreign language (EFL). The descriptive qualitative method and the random sampling technique were used in this research. The participants in this research were third-semester students of the English Education Department at the University of Mataram, and the instruments used were questionnaires and interviews. The result of this research showed positive perceptions. The positive perception is that they think social media are helpful and make it easy to learn English because social media are easy to access anywhere and everywhere, and the negative perception is that students think social media are effective but sometimes often create misunderstandings. Kinds of social media that students often use are YouTube, Instagram, and WhatsApp. Those applications are chosen because of their popularity and their ability to provide an endless amount of English input to them. The ways students use social media to learn English are by communicating with their friends to practice their language or joining the English group from their account, watching videos, listening to songs in English, and they also follow some accounts to learn English. The last advantage, after using social media to learn English, is to improve their English skills, especially vocabulary, grammar, etc. The challenges identified are truthfulness/or validity of information from social media, and the frequent distracting content that makes students forget their original intent of learning when using the social media.